Efektivitas Penggunaan Cuka Apel (Apple Cider Vinegar) Terhadap Daya Hambat Pertumbuhan Staphylococcus Aureus Yang Diisolasi Dari Ulkus Diabetes Mellitus - Alfiah Novianty; Agrijanti Agrijanti; Ari Khusuma (Poltekkes Kemenkes Mataram, 2021)
Diabetic ulcers are a chronic complication of Diabetes Mellitus in the form of open sores on the surface of the skin. Staphylococcus aureus bacteria is one of the bacteria that causes infection in wounds. Staphylococcus aureus bacteria will flourish in areas that have infections. An increasingly severe infection will cause gangrene. As it is known that Apple vinegar contains chemicals that are as antibacterial. Therefore apple vinegar can be used as a treatment in inhibiting the growth of Staphylococcus aureus bacteria. This study used a quasi-experimental design with 6 treatments, namely Tetracycline Antibiotics as a negative control of growth, sterile aquadest as a positive control of growth and apple vinegar with concentrations of 100%, 50%, 25%, and 12.5%. Then performed a statistical test using Kruskal Wallis with a confidence level of 95% or α = 0.05. Result: Sample Diabetic Foot Ulcer positively contained Staphylococcus aureus. Test the sensitivity that is done by using vinegar apple effective to inhibit the growth of Staphylococcus aureus at concentrations of 50% with a power resistor of 21.75 mm and a concentration of 100% by 24 mm. Conclusion: Apple Cider Vinegar effective to inhibit the growth of Staphylococcus aureus was isolated from Ulcer Foot Diabetic.